Inkspell - Funke, Cornelia Caroline; Bell, Anthea (New York : Scholastic, 2007)
Now thirteen, Meggie "reads" herself into Inkworld, where she, her family, and the characters in the book face chaos and danger as the original creator of the world frantically tries to redirect the story.
Translation of: Tintenblut / Germany : Cecille Dresler Verlag, 2005.
Originally published: Frome, Somerset, [England] : Chicken House, 2005.
Keywords: Books and reading -- Fiction; Authorship -- Fiction; Characters in literature -- Fiction; Bookbinding -- Fiction; Magic -- Fiction